2020
DOI: 10.1116/6.0000057
|View full text |Cite
|
Sign up to set email alerts
|

XPS guide: Charge neutralization and binding energy referencing for insulating samples

Abstract: This guide deals with methods to control surface charging during XPS analysis of insulating samples and approaches to extracting useful binding energy information. The guide summarizes the causes of surface charging, how to recognize when it occurs, approaches to minimize charge buildup, and methods used to adjust or correct XPS photoelectron binding energies when charge control systems are used. There are multiple ways to control surface charge buildup during XPS measurements and examples of systems on advanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
109
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(117 citation statements)
references
References 58 publications
8
109
0
Order By: Relevance
“…†† †† The problem of ionization-induced charging is well-known in solid insulator studies and is usually sufficiently counteracted using neutralization instrumentation such as electron flood guns. 95 Notably, the charging of the surface of a volatile, flowing aqueous solution in a low-vacuum environment cannot be compensated in this way. In order to accurately and generally perform the E F referencing procedure, the electrons from the metal sample would also need to be detected following traversal of the solution–vacuum interface, for example using a PES-compatible solution-on-metal sample system incorporating a continuous solution flow (to avoid sample contamination and cumulative photo-induced degradation).…”
Section: Lj-pes From Water and Aqueous Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…†† †† The problem of ionization-induced charging is well-known in solid insulator studies and is usually sufficiently counteracted using neutralization instrumentation such as electron flood guns. 95 Notably, the charging of the surface of a volatile, flowing aqueous solution in a low-vacuum environment cannot be compensated in this way. In order to accurately and generally perform the E F referencing procedure, the electrons from the metal sample would also need to be detected following traversal of the solution–vacuum interface, for example using a PES-compatible solution-on-metal sample system incorporating a continuous solution flow (to avoid sample contamination and cumulative photo-induced degradation).…”
Section: Lj-pes From Water and Aqueous Solutionmentioning
confidence: 99%
“… †† The problem of ionization-induced charging is well-known in solid insulator studies and is usually sufficiently counteracted using neutralization instrumentation such as electron flood guns. 95 Notably, the charging of the surface of a volatile, flowing aqueous solution in a low-vacuum environment cannot be compensated in this way. …”
Section: Lj-pes From Water and Aqueous Solutionmentioning
confidence: 99%
“…differential surface charging). 27 The XPS derived N/O ratios for [omim]Cl ionogels showed a large decrease from 16.6 to 6.5 when increasing the PEGDA content from 5-40 wt%. However, there was only a small amount of oxygen at the surface-1.8 at% for 40 wt% PEGDAwhich demonstrated that [omim]Cl ionogels surfaces were ionic liquid rich.…”
Section: Resultsmentioning
confidence: 95%
“…1.6 eV lower than that of metallic Pt, and whilst such anomalous values have been observed for PtAu alloys of varying composition and attributed to localisation of s-d bands [39], equally low values have also been observed for Pt supported on Al2O3 [40], indicating a possible preferential interaction with the alumina substrate and bimetallic PtSn/Al2O3 catalysts. However, given the Pt(4d5/2) value was consistent with that for metallic Pt, we considered this to be an effect of two distinct charge states, which we attributed to regions of different thicknesses (or island sizes) of SnO2 as implied by the Sn(3d5/2) binding energy discussed previously [41][42][43]. Assuming an ideal Pt/Pd ratio of 0.25 based on the metal loadings, then no direct correlation with Pt/Pd ratio and activity was For all catalysts, the percentage of Sn added to the alumina was the same; however, it is clear from Figure 10 that the Sn(3d) signal intensity changed markedly, which is related to the dispersion of Sn, with the most intense signal coming from the lowest-weight loading (Figure 10e), and is attributed to the wetting of the alumina beads by the SnO 2 .…”
Section: Catalyst Characterisationmentioning
confidence: 88%